2014
DOI: 10.1136/jmedgenet-2014-102423
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of serum levels of prostate-specific antigen in the Japanese population

Abstract: Rs16856139, associated with the expression of SLC45A3, is significantly associated with the levels of PSA in the Japanese population. Classification of subjects based on PSA genetic determinants would improve screening ability of PSA to detect PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Recently, it has been reported that genetic factors may play in role in the differences of PSA levels between Asians and Western populations. A GWAS in the Japanese population [43] illustrated that SNP rs16856139 is significantly associated with the levels of PSA in the Japanese population, yet the genetic differences in PSA levels between different populations are yet to be unveiled.…”
Section: Diagnosis Of Prostate Cancer In Asian Countriesmentioning
confidence: 99%
“…Recently, it has been reported that genetic factors may play in role in the differences of PSA levels between Asians and Western populations. A GWAS in the Japanese population [43] illustrated that SNP rs16856139 is significantly associated with the levels of PSA in the Japanese population, yet the genetic differences in PSA levels between different populations are yet to be unveiled.…”
Section: Diagnosis Of Prostate Cancer In Asian Countriesmentioning
confidence: 99%
“…Recently, Chinese researchers identified a novel genetic variant in the SLC45A3 gene that was associated with the level of serum PSA in a genome-wide association study (GWAS) [ 19 ]. Their discovery was confirmed in a study of a Japanese population [ 20 ]. A GWAS in a European population showed that a total of six loci were associated with PSA level [ 21 ], but two of them were not confirmed in Asian populations.…”
Section: Discussionmentioning
confidence: 88%
“…It was recently confirmed in two genome-wide association studies in Chinese and Japanese that the single nucleotide polymorphisms that may influence PSA level in healthy men were different from the Western population. 23 24 …”
Section: Discussionmentioning
confidence: 99%